The creeping man [anglicky] - Doyle, Arthur Conan Sir 1859-1930; Bellucci, Arianna (Illustrator); Baudet, Stephanie, 1945- (Leicester : Sweet Cherry Publishing, 2021)
If conveniet, come to Baker Street at ONCE. If incovenient, come anyway. Holmes. When Watson rushes to Baker Street only to find it is for a case about a professor´s misbehaving dog, he is not pleased...
Includes QR code to access audiobook.
Formerly CIP.
Keywords: Holmes, Sherlock -- Juvenile fiction; Watson, John H. -- (Fictitious character) -- Juvenile fiction; Detective and mystery stories; Children's stories; detektívky, trilery; literatúra pre deti a mládež; cudzojazyčná literatúra; čítam si sám (7+)